Using Pair Work to Improve Students` Ability in Speaking English - Biringkanae, Amelia (FKIP Universitas Khairun, 2025)
Using Pair Work to Improve Students` Ability in Speaking EnglishAmelia BiringkanaeE-mail: ameliabiringkanae30@gmail.com Abstract Speaking is productive skill. Speaking as a skill which enables us to produce utterance, when genuinely communicative. Compare with other language skills of second language, speaking is considered to be most difficult to acquire. In language teaching, there are some problems in improving students` speaking skill, especially in English. The problems are the lack of teachers' ability in teaching speaking and the shyness of students to speak in English. The purpose of this study is to know that whether the use of pair work can improve the students` ability in speaking English and their productivity in expressing ideas through pair work strategy. The data are from the students by given oral test. The test divided into two types, namely pre-test and post-test. The pre-test is the speaking test given before treatment. The second test is post-test namely a speaking test through pair work. The results of the quantitative analysis of the data revealed two categories of speaking problem, i.e. problems related to the students` self-confidence in speaking and the teacher (keeping, controlling and helping students to make on effective activities to improve students` speaking ability). Keywords: Pair work; Speaking ability. INTRODUCTION Language can not be separated from human life because all aspects of human life are related to language. By using language, someone can express his or her ideas, thoughts and feelings as well as get information. Without language it is impossible for someone to interact with others perfectly. We cannot deny that mastering speaking is not easy, so learners need extra efforts to master the skill. Speaking skill has become the most prioritized because it involves active ability to speak, i.e., producing spoken English rather than just receiving or reading (Jalaluddin, 2022). The same that other opinion, Speaking skill as the leaner`s ability to produce spoken English, not just listen or read in a way that is meaningful and communicative (Syafii, 2019). In language teaching, there are some problems in improving students` speaking skill, especially in English. The problems are the lack of teachers' ability in teaching speaking and the shyness of students to speak in English. Therefore, English teacher are demanded to be more creative in presenting their lessons.There have been some researches carried out or conducted research about language learning and teaching. For instance, Li Hui (2020) reported that there are some problems faced by the students and teachers in teaching and learning process. Firstly, the text books chosen as teaching materials in the speaking class were long sentence-based stories without providing any communicative or meaningful activities to prompt the students` speaking ability. Secondly, the speaking class was teacher centered. It was the teacher who did most of their talk. The teacher often conveyed the content or knowledge of the text book to the students without letting the students make their own practice. Thirdly, the students were reluctant to speak in the speaking class. Fourthly, because of the environment condition and also because the English language has different grammar structure from Indonesia, it was not easy for the students to speak it as fluently as their native language. In addition, Wayan (2018) also found some problems in teaching and learning process especially in speaking skill. In some cases they perhaps know about some vocabulary that they needs to express about some information or expression but they afraid to make mistake in pronunciation or structure or they feel shy to their friend when do a mistake. In the other cases they know about structure but they have limited vocabulary. The last is that the teacher dominates the teaching activity using Indonesian so it cannot increase students’ speaking skill. From all statements above it can be concluded that there are three major causal problems in teaching and learning speaking. First, the difficulty in the determination of the materials in teaching and learning process. Second, the lack of students` self-confidence in speaking English. Third, the lack of students` knowledge in grammar and vocabulary.However, these reports are not convinced because they just focus on identifying the problems of the students faced in teaching and learning process. Their reports might have been more useful if they had provided adequate explanation for some important efforts required to solve the reported problems. Briefly, such an explanation would be very useful for teachers to design a good and effective strategy in teaching to improve English learning outcomes at junior high school because the teachers are not only informed the problems faced by the students in teaching and learning process, but also given solution to made good English atmosphere in classroom to improve students’ English speaking ability at junior high school.To make successful teaching learning activities, especially in improving students' ability in speaking, the researcher have to find a good and effective strategy in teaching speaking namely pair work. Pair work is one of teaching strategy which can be used in teaching speaking to improve students' speaking skill. It means that the students working together in pairs. In pair work the students working together to finish their assignment in pairs and solve the problems in studying speaking. With using this strategy, we can make students more active and braver to speak in English. It can also make the students able to act in different situations. Burns (1997 : 43) stated that language learning is a dynamic and creative process. As teacher, we strive to create authentic situation inside the language classroom the language domains. So, in teaching and learning process the teachers need to design an effective strategy in teaching to improve students` speaking ability. To support the statement above, Michel, et al., (2009) stated that the passive method may not be the most effective way for students to learn. Similarly, Michel and Colleagues (2009) stated that students in the “active” course were better at learning and memorizing course material than students in the “passive” course.As a result, this study provides one of teaching strategy, namely pair work to makes the students active in produce word. Four lessons of teaching materials have been tried out to a number of the first year students at SMPN 2 Saluputti and resulted in the students` speaking skills improvement. The researcher believe that pair work strategy can be used by other English teachers to make an affective teaching and learning activities in order to improve students` speaking ability. In addition, the main advantage of pair work strategy is improve the students` self-confidence in speaking.LITERATURE REVIEW Pair work started getting attention of educationist in the 70s. In 70s educationists were concerned about increasing teacher talking time in language classes. During the 1980s and 1990s the development of communicative language teaching brought an important change in the role of students (Nunan Lamb 1996). Working together is worthwhile as “pair work immediately increase the amount of students talking time” (Harmer, 1991). Researchers are convinced that the students who take the initiative in learning learn more things and learn better than those who sit at the feet of teachers passively waiting to be taught (Knowles as cited in Hedge, 2000). Researchers reported that it is a source of intrinsic motivation for students as working in pair is fun for them. It provides the students with the opportunity to communicate with each other to share “suggestions, insights, feedback about successes, and failures” Researchers also claim that a teacher’s dominance in class makes it dull and it kills the students’ interests (Kundo Tutto, 1989). Traditionally the teacher method is used by the teachers for teaching English. The classes are overcrowded and teacher student interaction is rare. In fact, here the teacher acts like a dictator not a facilitator.However knowing a subject is one thing and teaching it is another. Teachers who are not trained cannot teach effectively as they do not know the techniques of teaching. Tiberius (1995) was of the opinion that pair work can fail due to several reasons; he mentioned students being exam oriented, teachers’ authoritative role in class and their lack of interest due to incompetence to handle pair work. In addition, Weaver and Hybles (2004) believed that “all the students do not like discussions, some find them boring and time consuming”. Although it is during pair work that a lot of real learning takes place since the students can use language really to communicate with one another. There are a number of causes of difficulty for teachers, which include the adaptation of new textbooks, the introduction of pedagogical reforms that teachers have not been trained to implement and the new teacher-learner relationship in the classroom.There are some previous researches which had examined speaking strategy that the teachers used in teaching and learning process. Efrizal (2012), for example, conducted a research on improving students’ speaking through communicative language teaching method at Mts Ja-alhaq, Sentot Ali Basa Islamic Boarding School of Bengkulu, Indonesia. In his study, the researcher used one strategy in improving students` speaking ability namely communicative language teaching method. During teaching and learning process of CLT, students are hoped to communicate orally and conquer all components of communicative competence and teacher is being motivator, assessor, facilitator, and corrector during students discussion or speaking in front of the class. It means this strategy make students more active and braver to speak in English. However, learning activities in CLT focuses on real oral communication with variety of language without to focus on form of grammatical patterns. As we know that, communicative proficiency involves knowledge and application of grammar and use of appropriate vocabulary of the language to convey meanings in a socially acceptable way. Grammar is the base of English language. English especially as a second or a foreign language is not acquired naturally; instruction and structured learning are important. Through grammar, an ESL learner learns how to operate at the sentence level and studies the governance of the syntax or word orders that are the rule of the game in the language and it cannot be denied that if one hopes to acquire and use English language accurately and fluently, grammar learning is necessary.The results of this study not only clarify the usefulness of this strategy in improving students` oral communication, but also find a good and effective strategy in teaching speaking. This strategy can activated teaching and learning process, because this strategy can help the students to develop their self confidence, working in pair encourage the students to be more concentrate on the lesson, and the students will interesting learning. In addition, pair work encourages the students to share their ideas and knowledge. It trains the students to work together. In this case, the students who have higher level skill can help the lower on. Therefore, this strategy can help teachers to design a good and effective strategy in teaching speaking so that students` speaking ability achieved. METHODOLOGY Participants The population of this research used all the second year students of SMPN 2 Saluputti who registered in academic year 2012/2013. There were 124 students. In taking of the sample in this research, it used purposive sampling. The sample was the students have had a pair work. There were 12 students. Research Design In this study, pre-experimental research design was used to construct this study. The design of the pre-experiment is critical for the validity of the results. Check whether the groups are different before the treatment starts and the effect of the treatment.Instrument In this research, the writer used a test as the instrument to collect data. It was given to the students to know their ability in speaking. The test was divided into two types, namely pre-test and post-test. The pre-test was the speaking test given before treatment. In this test, the students talking about the topic in the class. The second test was post-test, namely a speaking test through pair work. Procedures In this research, there are three procedure that the researcher have to do to collected data. First, the researcher gave the students pre-test. In this stage, the researcher explained what the students are going to do. The purpose of this test is to find out the students` speaking ability before treatment. Second, the researcher treated each pairs. After that, the researcher give the material related to speaking which they have to talk with their partner and the researcher ask some pairs one by one to retell what they have done in front of the class. Third, the researcher give post-test. It was purpose to find out the students’ speaking ability after giving explanation and practice about the strategy. Data Analysis In analyzed data, during the research, the researcher recorded all activities in the class research and scoring students using three component in speaking test by Heaton (1988;100). Table 1. Accuracy NoClassificationScoreCriteria1 2 3 4 5Excellent Good Fair Inadequate Inacceptable5 4 3 2 1Pronunciation is only very slightly influenced by the mother tongue, two or three minor grammatical and lexical errors Pronunciation is only very slightly influenced by the mother tongue. A few minor grammatical and lexical errors but most utterances are correct Pronunciation is still moderated influenced by the mother tongue but not serious phonological errors. A few grammatical and lexical errors but only one or two major errors causing confusion Pronunciation is influenced by the mother tongue but only a few serious phonological errors. Several grammatical and lexical errors, some of which cause confusion Pronunciation is seriously influenced by the mother tongue with errors. Several grammatical and lexical errors, some of which cause confusion. Table 2. Fluency NoClassificationScoreCriteria1 2 3 4 5Excellent Good Fair Inadequate Inacceptable5 4 3 2 1Speech of fluent and effortiess as that of a native speakerSpeed of speech to be slightly affected by language problemsSpeed of speech to be slightly strongly by language problemsUsually hesitant, often forced into silence by language limitationsSpeech is halting and fragmentary as to make conversation virtually impossible. Table 3. Comprehension NoClassificationScoreCriteria1 2 3 4 5Excellent Good Fair Inadequate Inacceptable5 4 3 2 1 Appears to understand everything without difficulty.Understand nearly everything at normal speed, although occasional repetition may be necessary understand of what is said at lower that normal speed with repetitionsHas great difficulty following what is said Can comprehend only social conversation spoken slowly and with frequent repetitions Cannot be understood even simple conversation English To measure the dependent variable the researcher classified the students’ score into five levels.4.1 – 5.0 classified as excellent3.1 – 4.0 classified as good2.1 – 3.0 classified as fair1.1 – 2.0 classified as inadequate0 – 1.0 classified as inacceptable To know the students ability in speaking English the writer find out the mean score of all students by using mean score formula (Gay, 1981:238). Notation : = mean score ∑ x = the sum of all score N = the total of sample FINDINGS By paying attention to the procedure to collect data, the writer would like to flatten the result of the data observed where has been stated in the technique in collecting data. In learning speaking by using pair work strategy, it showed there was improvement to students’ ability. Students’ speaking skill consisted of three components, such as, accuracy, fluency and comprehensibility. In Pre-Test, students’ ability classified as inadequate criteria. It can be shown that the average of students’ speaking ability in pre-test was 1.72 (table 1) and the percentages of the students` accuracy classified as inadequate classification (table 2), students` fluency classified as inadequate and inacceptable classification (table 3), and students` comprehensibility classified as inadequate and inacceptable classification (table 4). Whereas, students’ ability in post-test leaded into Good criteria (average score: 3.47) (table 5), which the percentages of component of students’ speaking evaluation in post-test was classified as good criteria; students` accuracy classified as fair and good classification (table 6), students` fluency classified as good classification (table 7), and students` comprehensibility classified as good classification (table 8). The results of analysis of students’ speaking ability had gotten an increase and a confirmation that using pair work as an effective strategy to improve students` speaking ability. DISCUSSION The discussion as an interpretation of the result of the data analysis and describes the students ability in speaking after applying the pair work strategy. This section deals with the discussion of using pair work strategy in speaking skill for junior high school students. It shows that there is an improvement for students’ speaking skill. The results show that in speaking skill, the three components in the pre-test such as accuracy, fluency, and comprehensibility describe the students’ speaking skill position. It is regarded that the average of speaking skill was 1.72 indicates students’ skill classified as inadequate classification. Here, the students have inadequate knowledge how to communicate effectively in English. So, they needs treatment to make their skills improve; allowing students to communicate in English with their partner.In other hand, after giving a treatment that is using pair work strategy to communicate in English with their partner, students get improvement to their achievement (average score: 3.47), followed by the improvement of the speaking component. It is needed to know that among speaking components, fluency achievement that has a big difference of score. It indicates that pair work strategy not only for learning how to communicate in English, but also for learning to increase the eloquence of students in speaking English because they will be interact with others around the world.Based on the concept of speaking, there are some of linguistic elements and nonlinguistic element of speaking. In linguistic elements there are vocabulary, pronunciation, accuracy, and fluently. And in nonlinguistic elements are concerned with some affective factors involve in speaking. Vocabulary is the first thing that we have to have in learning language. Vocabulary must be an important thing to be concerned. It should be mastered when a students need to develop his speaking ability. This statement is supported by Berlin in Hidayat (2008 : 16) stated, ``Vocabulary is one of the significant components of learning. Vocabulary building is very important in any foreign language learning, not only because it has a close relationship with intellectual maturity of the learners but also because the fact that it can improve the four language skills of the students without grammar very little can be conveyed``.As well as pronunciation is also an important element of language to learn. Audiolingualism method argues that native like pronunciation is one of the most important aspects of language proficiency. Ueno (1994 : 18) reports in Brown and Nation (1997 : 18) ``The research of this issue is inconclusive.in a recent survey, almost half of the recent experiments on this subjects show improvement in students` production of target language sounds``.Besides, Accuracy is the ability to speak properly that is selecting the correct words and expressions to convey the intended meaning, as well as using the grammatical pattern of English (Nunan, 2005 : 5). Not only accuracy but also fluently that needed in improving the proficiency of speaking. This fluently focuses on the appropriate of students or learners in speaking. Fluency refers to the capacity to speak fluidly, confidently, and at rate consistent with the norms of the relevant native speech community (Nunan, 2005 : 20). The way in which we respond to students when they speak in a fluency activity will have a significant bearing not only on how well they perform at the time but also on how they behave in fluency activities in the future (Harmer, 1991 : 20).The results can be generalized to recommend that using pair work can be used as an effective strategy to improve students’ speaking ability in junior high school level. CONCLUSION Speaking is one of main basic skills in learning English because it has an important role in human life. There has been many strategy to use in improving speaking skills but the writer believe that pair work strategy will provide students with adequate knowledge in mastering speaking as it gives students individual opportunities to practice and improve speaking skills. Furthermore, students have confident to speak and not worried about making mistake and error, then give them good model how to speak naturally in daily context and formal situation as well. In the future, their abilities will be a potential factor that can be used in the upper level of study. ACKNOWLEDGMENTS Praise to be to the Almighty Lord, intended for the blessings, health, and also inspirations provided to the author for the completion of the final project. The author also express her thanks and gratitude to her lectures, parents and friends for their valuable help, guidance, correction, and suggestions for the completion of this journal. REFERENCES Burns, Anne Joyce, Helen. (1997). Focus on Speaking. Macquarie University. National Centre for English Language Teaching Research. Harmer, Jeremy. (1991). The practice of Language Tests. London : Longman. Third Education. Hidayat, Ahmad. (2008). The Effectiveness of Self-assesment Techniques in Improving Students` English Speaking Proficiency. Thesis. Jalaluddin, J. (2022). Improving Indonesian Students Speaking Skill Through English Dormitory. Nusantara Hasana Journal, 2(6), 76-82. Li Hui, Li. (2020). Improving Students English Speaking Skill through Content-Based Instruction. Thesis Sebelas Maret University, Surakarta. Michel, N., Cater III, J. J., Varela, O. (2009). Active versus passive teaching styles: An empirical study of student outcomes. Human Resource Development Quarterly, 20(4), 397-418. Nunan, D Lamb, C. (1996). The self-directed teacher: Managing the learning process. Cambridge: Cambridge University Press. Nunan, D. (2005). Practical English Language Teaching. Singapura: MC Graw Hill. Syafii, M.L.,Sugianto,A., Cendriono, N.(2019). Improving Students` Speaking Skill by Using Multimedia Presentation Strategy. English Review: Journal of English Education, 7(2), 125-132. Doi:10.25134/erjee.v7i2.1690 Wayan. (2018). Improving Speaking Skill through Cooperative Learning Method. Thesis Mahasaraswati Denpasar University, Denpasar. Appendix Table 1. The students` score in pre-test. Number of StudentsAccuracyFluencyComprehensionTotalStudent`s Score132382.7211241.3322262432272.3522151.7622372.3721251.78111319111311021141.31121141.31222262Total2318216220.7 Table 2. The criteria and percentages of the students` accuracy. NoAbility ClassificationScoreNumber of StudentsPercentage12345ExcellentGoodFairInadequateInacceptable54321–273–16.7%58.3%25%Total12100% Table 3. The criteria and percentages of the students` fluency. NoAbility ClassificationScoreNumber of StudentsPercentage12345ExcellentGoodFairInadequateInacceptable54321—66—50%50%Total12100% Table 4. The criteria and percentages of the students` comprehensibility. NoAbility ClassificationScoreNumber of StudentsPercentage12345ExcellentGoodFairInadequateInacceptable54321–255–16.6%41.7%41.7%Total12100% Table 5. The students’ score in pos-test. Number of studentsAccuracyFluencyComprehensionTotalStudent`s Score1444124244412434441244334103.353339364441247344113.783339393339310343103.311334103.31233393Total40424312541.7 Table 6. The criteria and percentages of the students` accuracy. NoAbility ClassificationScoreNumber of StudentsPercentage12345ExcellentGoodFairInadequateInacceptable54321-48—33.3%66.7%–Total12100% Table 7. The criteria and percentages of the students` fluency. NoAbility ClassificationScoreNumber of StudentsPercentage12345ExcellentGoodFairInadequateInacceptable54321-66—50%50%–Total12100% Table 8. The criteria and percentages of the students` comprehensibility. NoAbility ClassificationScoreNumber of StudentsPercentage12345ExcellentGoodFairInadequateInacceptable54321-75—58.3%41.7%–Total12100%